Effects of the injection strategy on the mixture formation and combustion characteristics in a DISI (direct injection spark ignition) optical engine. (15th December 2015) - Song, Jingeun; Kim, Taehoon; Jang, Jihwan; Park, Sungwook
Abstract: The present study investigates the effect of the injection strategy on the mixture quality and the consequential combustion characteristics. The injection strategies considered in the present study were divided into two parts: single injection (with a wide range of injection timings during the intake stroke) and double injection (with a short second injection during the compression stroke). The in-cylinder pressure and high-speed flame images were acquired to evaluate the combustion characteristics, and KIVA simulation was conducted to observe the in-cylinder flow and the fuel spray spreading procedure. For the single injection, retarding the injection timing caused an increase in the combustion speed and in-cylinder pressure. In this case, the major factor that increased the in-cylinder pressure was the turbulence intensity; the later injection produced a stronger turbulence at the spark timing, which caused a higher in-cylinder pressure. Meanwhile, the flame propagation direction was mainly affected by the equivalence ratio distribution. The flame speed toward the fuel-lean region was significantly slower than toward the fuel-rich region. The double injection strategy utilized the additional turbulence induced by the spray motion to increase the engine power. Highlights: In-cylinder pressure increases as the injection timing is retarded. Turbulence intensity induced by the spray motion increases the flame speed. Flame propagation direction is highly affected by the local fuel concentration. Split injection can increase engine power by supplying additional turbulence.